Corporate taxation in the OECD in a wider context - Loretz, S (2008)

(untitled)
Against the background of increased globalization statutory corporate tax rates have shown a clear downward trend over the last two decades. The sharp decline in these rates was accompanied by substantial tax base broadening and a comparable reduction in personal income tax rates only until the early 1990s. This suggests that corporate tax competition is of increasing importance. So far corporate tax revenues remain fairly stable. But an analysis of corporate taxation in the context of the overall tax systems shows that a substantial shift towards value-added taxes has taken place. While the trends so far have been driven by smaller European countries, recent tax reforms indicate that increasing tax competition is inducing a shift towards consumption taxes even for larger economies.